PONDOK PESANTREN DAN RADIKALISME AGAMA (Studi Pada PPM. TMI Al Istiqamah Kabupaten Donggala) - Abdul Kadir R (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Donggala, Middle Sulawesi. The focusresearch is Pesantren TMI Al-Istiqomah. This research aims to describehow radicalism potency in this Pesantren. This use quantitative andqualitative method, where data was collected by using questioner to anumber students and interview to the teachers. The data was analyzedby descriptive analysis..This research indicates that there are some indicators posed at Pesantrenpotency don't embrace radicalism understanding, such as: attitudefrown upon hardness by bomb suicide action, even though with reasonof jihad. They also confess and respect the existence of other religionfollowers.